PENGARUH PEMBELAJARAN KOLABORASI DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS X SMA DAERAH 3T KABUPATEN SORONG - Nalole, Yasin; Tukiyo, Tukiyo; Dwi Bambang Putut Setyadi; Hersulastuty (Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to analyze the effect of collaborative learning and learning motivation on the reading comprehension skills of 10th grade high school students in the 3T (Frontier, Outermost, and Disadvantaged) areas in Sorong Regency. The method used in this study is descriptive with a quantitative approach. This descriptive method involves collecting data to test hypotheses or answer questions about public opinion on certain issues or topics. The population in this study included all 10th grade students of SMA Negeri 4 and SMA Negeri 8 Sorong Regency, with the research sample consisting of 10th grade students in both high schools. The sampling technique used was Purposive Random Sampling with a 5% error rate. By using the Slovin formula to determine the number of samples, it was determined as many as 120 out of 172 students. The data analysis technique was carried out with the help of the SPSS 25 application on data from the questionnaire regarding collaborative learning and student motivation towards reading comprehension skills, through reliability tests, correlation tests, homogeneity tests, validity tests, normality tests, linearity tests, and hypothesis tests. The results of the analysis showed that both collaborative learning and learning motivation had a significant influence on reading comprehension skills. The correlation test showed a value of 0.333, indicating that learning motivation has a stronger relationship to reading comprehension ability compared to collaborative learning. The results of the regression test showed that learning motivation has a greater influence than collaborative learning, with a regression coefficient value of 0.304 and a p value <0.001. This analysis confirms that effective learning strategies must integrate collaborative methods. In addition, this approach must also be able to increase student learning motivation. Therefore, teachers and schools need to develop programs that not only emphasize group-based learning but also encourage students' intrinsic motivation to improve reading comprehension.